Oral Nutrition Supplements: Regulasi dan Distribusi di Indonesia - Studi di Rumah Sakit Swasta di Surabaya: Oral Nutrition Supplements: Regulation and Distribution in Indonesia – a Study in a Private Hospital in Surabaya - Azzahra', Lama'ah; Widjaja, Nur Aisiyah; Nurfirdaus, Yasmine; Ardianah, Eva; Hermanto, Edi; Adha, Aziza Zahrotul (Universitas Airlangga, 2024)
Background: Oral Nutrition Supplements (ONS) in the Minister of Health Regulation No. 29 year 2019 which was made as the guidance of nutritional management for children with nutritional problems, especially growth failure (still prevalent) and became one of Indonesia governments’ goal for MDG’s achievement. Objectives: To describe the regulations and distributions of ONS as a strategy to reach the optimal catch-up growth in children under 5 years-old in private hospital in Surabaya based on the Minister of Health Regulation No. 29 year 2019. Also to determine the effect of ONS on insulin-like growth factor-1 (IGF-1) as a growth marker and lymphocytes as immune cells involved in immune response. Methods: A quasi-experiment with pre-post design involving children aged 12-60 months old. The subjects received 400 ml of ONS ( 400 kcal/day with estimated nutritional requirement of 1000 kcal/day) under the provision of the pediatrician as an adjuvant to cover their nutrients deficits. Results: ONS intervention along with dietary counselling for nutritional therapy and medication improved the children’s growths parameters, including body weight (from 10.38±2.28kg at day-0 to 11.27±2.38 at day-90, p-value=0.000) and body length/height significantly (from 82.94±9.58cm to 85.75±8.93 at day-90, p-value=0.000). ONS also improved IGF-1 in children with growth failure. Conclusions: ONS intervention was proved to improve the IGF-1 levels, but not with the number of lymphocyte cells. The regulation of ONS must be under professional provision as it has the effect to increase body weight rapidly and must be stopped when the children receive the prescription reached their catch-up growth.